Enhancing Cast Unit List Reports in Tekla Structures: A Guide to Template Modification - Ulfa, A. A; Pongtuluran, E. H (Jurnal MESIL (Mesin Elektro Sipil), 2025)
This paper offers a comprehensive guide for refining Structural Cast Unit Reports within Tekla Structures via template modification. Tekla Structures, a powerful Building Information Modeling (BIM) software developed by Trimble, specializes in creating detailed 3D models for structural engineering projects. The Volume Recapitulation Reporting System in Tekla Structures facilitates precise measurement and reporting of structural element volumes, streamlining material estimation, cost analysis, clash detection, and progress tracking. An intriguing observation in Tekla Structures version 2023 revealed ambiguous cast unit volume data, varying between users on the same project based on their modeling approaches. This highlights the critical need for examining the reporting system's accuracy and consistency. The guide outlines a step-by-step approach to customize cast unit reports, ensuring reliable volume calculations. The method entails independent modeling of a structure using Tekla Structures, revealing a discrepancy in total cast unit volume, prompting the need for template modification. The guide then details the template modification process, including accessing the Template Editor and incorporating a new calculation column. Results demonstrate a significant enhancement in volume reporting accuracy. By modifying the template, discrepancies in cast unit volume data are rectified, ensuring consistent and reliable reporting across different users and devices. In conclusion, customizing templates in Tekla Structures is essential for enhancing project management and communication. The findings emphasize the importance of accurate reporting, and future AI advancements may further streamline template adjustments. This guide offers practical steps to optimize Tekla Structures for consistent and reliable reporting.